Improving Learning Outcomes in Al-Qur'an and Hadith Studies through the Card Sort Method - Nur Arifin, Firli Oktavia (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2024)
In the learning process, an active and enjoyable learning environment is a key point for students to be interested in the material presented. However, in reality, students often feel bored because learning is mostly conducted using the lecture method alone. The subject of Al-Qur'an Hadith is not only about understanding but also about knowing and memorizing verses related to the material taught. Therefore, a teacher must be able to choose enjoyable teaching methods that can enhance learning outcomes and students' memorization abilities. One effective method to help students memorize and understand the verses of the Qur'an is the card sort method, which involves using index cards containing Al-Qur'an Hadith material that is then discussed in their respective groups. This aims to assess students' memorization strengths and understanding of the verses of the Qur'an they have studied. The type of research used is descriptive qualitative. The results of this study indicate that by using the card sort learning method supported by various other methods such as lectures, discussions, and question-and-answer sessions, students will be more active and enthusiastic in learning. The evaluation of the learning process can be seen from students' activity in discussions, cooperation with their groups, and their attitude in answering questions from the teacher. Thus, the card sort method can enhance students' understanding and memorization of verses related to the material and meet the desired targets.